SCALE DEPENDENCY IN SPATIAL PATTERNS OF SATURATED HYDRAULIC CONDUCTIVITY - Sobieraj J.A.; Elsenbeer H.; Cameron G. (My University, 2004)
This study investigates spatial patterns of Ks and tests the hypothesis of whether structural variance emerges from noise with increasing sampling precision. We analyzed point measurements of Ks along independent transects at sampling intervals of 25, 10, 1 and 0.25 m. The field area is a tropical rainforest catena (i.e. toposequence) characterized by systematic downslope changes in soil properties including color (red to yellow), mineralogy (kaolinite-illite to kaolinite) and texture (sandy clay to sand). Independent transects spanning the entire catena at lag intervals of 25 and 10 m reveal little to no spatial patterns in Ks; i.e. scatter plots are noisy and lack apparent spatial trends, and semivariograms suggest little to no autocorrelation in Ks. As sampling precision is increased (h=1 and 0.25 m), spatial patterns emerge in Ks for the downslope areas, in which distinctive hydraulic boundaries in Ks correlate with relatively small-scale, topography-controlled soils with coarse textures (>=80% sand). For these areas, semivariograms of Ks and those of %sand and %clay exhibit similar spatial structure characterized by small nugget variances and large ranges, and nugget variance is reduced as sampling precision increases from 1 to 0.25 m. In the upslope, clay-rich locations along this toposequence, Ks exhibits few spatial patterns, irrespective of sampling scale. For these locations, scatter plots are noisy without apparent spatial trends, and semivariograms show almost complete nugget variance, suggesting little to no correlation in this hydraulic parameter at any scale. This study suggests that in the absence of coarse textures (>=80% sand), there is little predictability in Ks, even at sampling intervals of 0.25 m. We believe this lack of spatial structure is due to a predominance of small-scale processes such as biological activity that largely control Ks in this forested setting.
Keywords: AMAZON BASIN; CATENA; SATURATED HYDRAULIC CONDUCTIVITY; SCALE; SPATIAL VARIABILITY; TROPICAL RAINFOREST